Prophylactic Evidence of MSCs-Derived Exosomes in Doxorubicin/Trastuzumab-Induced Cardiotoxicity: Beyond Mechanistic Target of NRG-1/Erb Signaling Pathway - Ebrahim, N; Al Saihati, HA; Mostafa, O; Hassouna, A; Abdulsamea, S; Abd El Aziz M. El Gebaly, E; Abo-Rayah, NH; Sabry, D; El-Sherbiny, M; Madboly, AG; Hussien, NI; Saadani, REH; et al. (MDPI AG, 2022)
Trastuzumab (Trz) is a humanized monoclonal antibody targeting epidermal growth factor receptor 2 (HER2; ErbB2). The combined administration of Trz and doxorubicin (DOX) has shown potent anti-cancer efficacy; however, this regimen may be accompanied by severe cardiac toxicity. Mesenchymal stem cells (MSCs)-derived exosomes are nanosized vesicles that play a crucial role in cell–cell communication and have shown efficacy in the treatment of various diseases. In this study, we aim to investigate the cardioprotective effects of MSCs-derived exosomes in a DOX/Trz- mediated cardiotoxicity model, and the possible mechanisms underlying these effects are elucidated. Forty-nine male rats were randomly assigned into four groups: Group I (control); Group II (Dox/Trz); Group III (protective group); and Group IV (curative group). Cardiac hemodynamic parameters, serum markers of cardiac injury, oxidative stress indices, and cardiac histopathology were investigated. Further, transcript profile of specific cardiac tissue injury markers, apoptotic markers, and fibrotic markers were analyzed using qRT-PCR, while the protein expressions of pAkt/Akt, pERK/ERK, pJNK/JNK, pJNK/JNK, and pSTAT3/STAT3 were evaluated by ELISA. Additionally, cardiac mirR-21 and miR-26a were assessed. A combined administration of DOX/Trz disrupted redox and Ca2+ homeostasis in cardiac tissue induced myocardial fibrosis and myofibril loss and triggered cardiac DNA damage and apoptosis. This cardiotoxicity was accompanied by decreased NRG-1 mRNA expression, HER2 protein expression, and suppressed AKT and ERK phosphorylation, while triggering JNK phosphorylation. Histological and ultra-structural examination of cardiac specimens revealed features typical of cardiac tissue injury. Moreover, a significant decline in cardiac function was observed through biochemical testing of serum cardiac markers and echocardiography. In contrast, the intraperitoneal administration of MSCs-derived exosomes alleviated cardiac injury in both protective and curative protocols; however, superior effects were observed in the protective protocol. The results of the current study indicate the ability of MSCs-derived exosomes to protect from and attenuate DOX/Trz-induced cardiotoxicity. The NRG-1/HER2, MAPK, PI3K/AKT, PJNK/JNK, and PSTAT/STAT signaling pathways play roles in mediating these effects.
Keywords: Trastuzumab; Doxorubicin; Stem cells; Exosomes; Cardiac toxicity; NRG-1; MAPK; AKT